Functional characterization of the type 2 diabetes associated variant rs3832490 in repin1 - Krüger, J; Weidle, K; Kern, M; Enigk, B; Prellberg, M; Müller, I; Schleinitz, D; Breitfeld, J; Tönjes, A; Stumvoll, M; Blüher, M; Kovacs, P; et al. (Diabetologie und Stoffwechsel, 2013)
Background/Aim: Repin1 maps within a quantitative trait locus for total cholesterol, body weight, serum triglycerides and serum insulin in the rat. Sequencing of human repin1 revealed a 12bp deletion within the coding region (rs3832490). We investigated the functional consequences of this variant. Methods/Materials: 1) Population genetic studies: The deletion in repin1 was genotyped for subsequent association studies in two independent cohorts: the Leipzig cohort (N = 1830) and the Sorbs (N = 1046). In addition repin1 mRNA levels were determined in paired human samples of visceral and subcutaneous adipose tissue (N = 86). 2) Functional studies: 3T3-L1 preadipocytes were transfected with plasmids carrying either the repin1-wildtype or the repin1-deletion . We tested two different methods for transfection, lipofection (GeneJammer) and electroporation (NeonTransfectionSystem). The transfection efficiency was examined by using FACS and the overexpression of both variants was checked by Western Blot. After the differentiation we stained the cells with oil red O. Results: 1) Compared with the non-carriers, subjects homozygous for the deletion variant seemed to be protected against type 2 diabetes (T2D) (P = 0.011, after adjusting for age, sex and BMI). This variant was also associated with body fat mass and fasting plasma glucose. Compared with non-carriers, subjects with the deletion had a lower maximum adipocyte size in visceral and subcutaneous fat (P = 0.065 and 0.014, respectively) and tended to have a lower mRNA repin1 expression in the subcutaneous fat. 2) Substantially higher transfection efficiency was achieved by electroporation when compared with lipofection (84.2% vs. 15.2%). Using microscopy, there was no visual difference between the repin1-deletion and repin1-wildtype transfected cells. Compared with the untransfected 3T3-L1 adipocytes the repin1 -transfected cells showed less and smaller lipid droplets. Conclusion: The variant in repin1 might reduce the risk for T2D most likely by influencing the adipocyte function and morphology. Furthermore, the study encourages further in vitro experiments in 3T3-L1 cells to pinpoint the role of the identified deletion in repin1's biology.